Ta có: \(x^3+y^{ 3}=\left(x+y\right)\left(x^2-xy+y^2\right)\ge\left(x+y\right)\left(2xy-xy\right)=\left(x+y\right)xy,\forall x,y\ge0\)
Áp dụng:
\(\sum_{cyc}\dfrac{1}{a^3+b^3+abc}\le\sum_{cyc}\dfrac{1}{\left(a+b\right)ab+abc}=\sum_{cyc}\dfrac{1}{ab\left(a+b+c\right)}=\dfrac{a+b+c}{abc\left(a+b+c\right)}=\dfrac{1}{abc}\)
\("="\Leftrightarrow a=b=c\)
Ta có: \(x^3+y^3=\left(x+y\right)\left(x^2+y^2-xy\right)\ge\left(x+y\right)\left(2xy-xy\right)=\left(x+y\right)xy\)( \(\forall x,y\ge0\) )
Áp dụng: \(\sum\dfrac{1}{a^3+b^3+abc}\le\dfrac{1}{\left(a+b\right)ab+abc}=\sum\dfrac{1}{ab\left(a+b+c\right)}=\dfrac{a+b+c}{abc\left(a+b+c\right)}=\dfrac{1}{abc}\)
\("="\Leftrightarrow a=b=c\)